Radiation Responses of Human Mesenchymal Stem Cells Derived From Different Sources - Ningning He; Changyan Xiao; Yuxiao Sun; Yan Wang; Liqing Du; Yu Feng; Yang Liu; Qin Wang; Kaihua Ji; Jinhan Wang; Manman Zhang; Chang Xu; et al. (Dose-Response, 2019)
Mesenchymal stem cells (MSCs) derived from different tissues may aid in the regeneration of radiation-induced organ lesions; however, the radiation responses of human MSCs from different sources are unknown. In our study, a comparison of the results from cell proliferation, apoptosis, cell cycle, DNA damage, and DNA repair assays consistently showed that MSCs derived from adipose tissue possess a significantly stronger radiation resistance capacity than MSCs derived from umbilical cord and gingival, which is accompanied by a higher level of phosphorylated signal transducer and activator of transcription 3 (Stat3) expression. This reminds us Stat3 could be a potential biomarker of radiation resistance. These findings provide a better understanding of radiation-induced biologic responses in MSCs and may lead to the development of better strategies for stem cell treatment and cancer therapy.